Case Study 4 - Poland : Participation in Macroeconomic Policy Making and Reform - World Bank (World Bank, Washington, DC, 2012)
In January 1999, Poland launched a new pension system that was the result of 5-6 years of broad outreach campaigns and complex negotiations within the government and between the government and key stakeholder groups. A number of compromises were made to broaden support for the reform; these changes will significantly increase costs during the transition period but without undermining the long-term viability of the reformed pension system. Post-communist Poland operated on a traditional pay-as-you-go (PAYG) system; payroll taxes of current workers financed the pension benefits of current retirees. Due to a number of policy changes expanding early retirement options and other privileges, pension costs skyrocketed in the mid-1990s and Poland had one of the highest spending rates of any post-communist transition country. In addition, long-term demographic shifts led to a decline in people paying into the system relative to those receiving benefits. Contribution rates (i.e., payroll taxes) had already risen from 25% in 1981 to 45% in 1990. They could not easily be pushed up further.